PENGARUH FORMULASI PASTA LABU KUNING DAN TEPUNG BERAS KETAN PUTIH TERHADAP SIFAT KIMIA DAN SENSORI DODOL [The Effect of Formulation Pumpkin Paste and White Glutinous Rice Flour on Chemical and Sensory Properties Dodol] - Hadi Hanggara; Sussi Astuti; Sri Setyani (Jurnal Teknologi & Industri Hasil Pertanian, 2016)
The objective of this research was to study the effect formulation between pumpkin pasta and white glutinous rice flour on chemical and sensory properties of dodol. The research was a single factor, arranged in a Complete Randomized Design with six replications. The factor was the formulation of pumpkin pasta and white glutinous rice flour consisted of four levels, i.e. 10 : 90 (L1); 20 : 80 (L2); 30 : 70 (L3); 40 : 60 (L4); 50 : 50 (L5); and 60 : 40 (L6).  The data were analyzed by using ANOVA and were further tested with LSD test at 5% level of significant. The results showed that the ratio of pumpkin paste and white glutinous rice flour significantly affected the chemical (moisture and sucrose contents) and  sensory properties (texture, color, taste, flavor and overall acceptance) of dodol.  The best formulation was found on dodol produced from 50% pumpkin paste and 50% white glutinous rice flour (L5) with the moisture content of 22,51%, sucrose content of 33,67%, total carotenoids content of 1,16 µg/g, fat content of 23,12%, with the texture score of 2,71 (rather elastic), color score of  3,97 (yellow-brown), taste score of 3,75 (feel pumpkin), flavor score of 3,50 (flavorful pumpkin) and the overall acceptance of 3,51 (like).Keywords:  dodol, pumpkin, white glutinous rice